Improving School Disaster Preparedness Through Teacher, Cadre Training and Disaster Simulation for Students at Public Elementary School - Satriya Pranata; Aric Vranada; Anna Kurnia; Risnatun Hasanah; Novita Andaresta Putri; Siti Juhro; Khani Fatul Khusna (Community Development Journal, 2023)
Based on its geographical location, Public Elementary School (PES) 1 Banyuroto, Sawangan, Magelang, Central Java is located in an area prone to volcanic eruptions and earthquakes. Because in general disaster hazards can occur at any time, it is very important for the school environment to improve its preparedness in disaster preparedness. One of the efforts that are considered the most strategic is through training and disaster simulation for cadres, school teachers and students to improve their ability to respond to disasters through disaster preparedness schools. The purpose of this activity is to realize the implementation of disaster management training activities and disaster simulation at PES 1 Banyuroto. The method used is a direct instruction to increase partners' understanding related to disaster and disaster mitigation materials, Forum Discussion Groups to develop disaster learning modules and simulations to improve the skills of disaster response partners. This activity was carried out at PES 1 Banguroto, Sawangan, Magelang, Central Java. The output targets resulting from this activity are the formation of evacuation route maps and their explanations and the preparation of disaster learning modules that can be used in the learning process and implementation of earthquake disaster simulations at PES 1 Banyuroto, Magelang, Central Java. The development of a disaster preparedness school program will effectively contribute to the early prevention of disaster hazards.